2009
DOI: 10.1111/j.1365-2958.2009.06664.x
|View full text |Cite
|
Sign up to set email alerts
|

HlyU acts as an H‐NS antirepressor in the regulation of the RTX toxin gene essential for the virulence of the human pathogen Vibrio vulnificus CMCP6

Abstract: SummaryIn Vibrio vulnificus, HlyU upregulates the expression of the large RTX toxin gene. In this work we identified the binding site of HlyU to -417 to -376 bp of the rtxA1 operon transcription start site. lacZ fusions for a series of progressive deletions from the rtxA1 operon promoter showed that transcriptional activity increased independently of HlyU when its binding site was absent. Thus HlyU must regulate the rtxA1 operon expression by antagonizing a negative regulator. Concomitantly we found that an hn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
85
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(86 citation statements)
references
References 62 publications
1
85
0
Order By: Relevance
“…However, lacZ fusion experiments demonstrated that HlyU regulation must occur by derepression, rather than by positive regulation, of the rtxA1 operon. That work also demonstrated that rtxA1 expression is normally silenced by the master regulator H-NS and that HlyU acts as a derepressor by displacing H-NS from its binding sites, thus relieving the repression of rtxA1 (13).…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…However, lacZ fusion experiments demonstrated that HlyU regulation must occur by derepression, rather than by positive regulation, of the rtxA1 operon. That work also demonstrated that rtxA1 expression is normally silenced by the master regulator H-NS and that HlyU acts as a derepressor by displacing H-NS from its binding sites, thus relieving the repression of rtxA1 (13).…”
mentioning
confidence: 84%
“…We also showed that the HlyU protein plays an essential role in its regulation. In its normal state, rtxA1 expression is repressed by the H-NS protein, and HlyU acts as a derepressor by binding to a region upstream of the rtxA1 operon promoter, resulting in the removal of H-NS and allowing rtxA1 expression and bacterial invasion to occur (13). However, an intimate knowledge of the intrinsic steps involved in the biological mechanism of action of HlyU is limited to predictions based on the recently solved crystal FIG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, nucleoid-associated protein (H-NS) binds DNA at lower temperatures blocking the transcription of multiple genes, whereas higher temperatures cause loosening in the DNA structure allowing transcription to occur. H-NS suppresses virulence-associated genes, such as RTX and CTX, in V. vulnificus (Liu et al, 2009) and V. cholerae (Stonehouse et al, 2011), respectively. The concurrent upregulation of H-NS (ZP_05887985.1) and RTX toxin (ZP_05887531.1) on CPI-1 in the Vc450 proteome at 27 1C could be the result of a conserved Vc450 H-NS unable to regulate a more recently acquired RTX toxin.…”
Section: Temperature-dependent Regulationmentioning
confidence: 99%
“…HlyU, which was identified by in vivo-induced antigen technology and is essential for V. vulnificus virulence in mice (11,19), is required for the expression of vvhA and rtxA1 and binds directly to a region upstream of the operon where rtxA1 is located (19,20).…”
mentioning
confidence: 99%